Impact of triaxiality on the rotational structure of neutron-rich rhenium isotopes - M.W. Reed; G.J. Lane; G.D. Dracoulis; F.G. Kondev; M.P. Carpenter; P. Chowdhury; S.S. Hota; R.O. Hughes; R.V.F. Janssens; T. Lauritsen; C.J. Lister; N. Palalani; et al. (Physics Letters B, 2016)
A number of 3-quasiparticle isomers have been found and characterised in the odd-mass, neutron-rich, 187Re, 189Re and 191Re nuclei, the latter being four neutrons beyond stability. The decay of the isomers populates states in the rotational bands built upon the 9/2−[514] Nilsson orbital. These bands exhibit a degree of signature splitting that increases with neutron number. This splitting taken together with measurements of the M1/E2 mixing ratios and with the changes observed in the energy of the gamma-vibrational band coupled to the 9/2−[514] state, suggests an increase in triaxiality, with γ values of 5°, 18° and 25° deduced in the framework of a particle-rotor model.